Pengaruh Motivasi Kerja, Reward dan Punishment terhadap Kinerja Karyawan PDAM Tirta Raja OKU - Rica Nurma Sari; Munajat Munajat; Rini Efrianti (Jurnal Ekonomi, Manajemen, dan Bisnis, 2026)
This study aims to analyze the influence of work motivation, rewards, and punishment on employee performance at PDAM Tirta Raja OKU. The research method used was quantitative, with data collection using a questionnaire. The population in this study was all 156 permanent employees of PDAM Tirta Raja OKU, with a sample of 61 respondents using accidental sampling. Data analysis was performed using multiple linear regression with the help of SPSS. The results showed that partially, work motivation had a positive and significant effect on employee performance. Rewards also had a positive and significant effect on employee performance, while punishment had a positive and significant effect on employee performance. Simultaneously, work motivation, rewards, and punishment significantly influenced employee performance at PDAM Tirta Raja OKU. The conclusion of this study is that increasing work motivation, providing appropriate rewards, and implementing fair and consistent punishment can improve employee performance. Therefore, companies are expected to optimally manage these three factors to achieve better employee performance.